Character Building Through Scout Training for Elementary School Students at Sanggar Bimbingan Sungai Mulia 5 - Ninda Mayada Ertha; Rima Nadila Adiningsih; Harun Joko Prayitno; Azura Lu’lu Firdausi (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
The Scout activities play a very important role in the development of a child's character because they not only provide lessons learned in school but also strengthen a child's character through various activities. The purpose of the service provided to students is to introduce scouting activities while also strengthening the character development of students through these activities. The method used is a qualitative approach. Data collection is done using several techniques, namely (1) open observation, (2) unstructured interviews, and (3) documentation in the form of documents related to the research focus, such as attendance lists and other supporting information according to the field conditions during the research. The results of this service show that through Scout activities, students are able to improve their character. Students increasingly understand how to implement the values of character found in scouting in their daily lives.